Compte rendu sténoqraphique de la soixante et unième séance (privée) . Stenographic Summary of the 61st Session (Private) - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations Special Committee on the Problem of Hungary Witness XXX, an agrarian engineer and university professor, made a statement. He talked about the outbreak of the revolution in Debrecen, the Soviet intervention and the atrocities committed by the ÁVH and NKVD in Hungary. The committee asked him about the events he participated in, his information sources, and the power structure in Hungary before and during the revolution. The committee finished the hearing of witnesses. Next, they will meet in New York to discuss the report.